Implementation of Green Supply Chain Management Practices in Uzbekistan. - Shahparan, Mohammad; Klykov, Artem (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
reen supply chain management (GSCM) practices are essential in ensuring the sustainability of the supply chain while minimizing the negative environmental impact. This paper investigates the implementation of GSCM practices in Uzbekistan. The research objective is to assess the current status of GSCM practices in Uzbekistan and identify the challenges and opportunities for implementing GSCM practices in the country. The research methodology involves a mixed-methods approach, including a survey of supply chain managers in Uzbekistan and a review of academic and industry literature. The results indicate that the implementation of GSCM practices in Uzbekistan is still in its early stages, with several challenges faced by supply chain managers, including a lack of awareness, limited resources, and a lack of regulatory support. However, opportunities for improving GSCM practices in Uzbekistan were identified, including stakeholder engagement, training and education, and government support. Drawing on the rich literature, an attempt is made to present the needs for GSCM practices and organizational environmental sustainability.